The Role of Needs Analysis in English for Academic Purposes in Higher Education - Paola Clara Leotta; Tamari Dolidze (European Scientific Journal, ESJ, 2022)
Despite the established importance of English worldwide, and notwithstanding the fact that in expanding circle countries (defined as expanding or extending circle countries those countries where English is used as a foreign language), English for Academic Purposes plays an increasingly important role. Studies on the linguistic needs of university students are still lacking their perspective, at least in Italy, where students studying English language in Higher Education institutions are expected to gain access to the discourses of the academia via language competence. For this reason, the present paper reviews the theoretical and practical bases of English for Academic Purposes in order to provide further thought-provoking ideas based on a study carried out in the Italian university context. As far as method is concerned, due to the spread of the COVID-19 pandemic, the study was conducted through Google Forms. The results of the authors’ questionnaire model are presented and analysed for the purpose of this research. Findings demonstrate both the complex network of elements that play a significant role in determining the needs of EAP students in Italy, and the unavoidable necessity to set priorities. It is a fact that needs in a learner-centred system are not static. In addition, learning EAP is bound to mean learning to be an independent learner.